2019
DOI: 10.1186/s12911-019-0803-2
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone applications to overcome malnutrition among preschoolers: a systematic review

Abstract: Background Malnutrition is one of the most important reasons for child mortality in developing countries, especially during the first 5 years of life. We set out to systematically review evaluations of interventions that use mobile phone applications to overcome malnutrition among preschoolers. Methods The review was conducted and reported according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses: the PRISMA statement. To be eligible, the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
(35 reference statements)
0
6
0
1
Order By: Relevance
“…In the other field of diagnosing genetic diseases, facial‐photograph‐based e‐health technology has also showed it potential 37,38 . In the field of screening malnutrition, more and more mobile phone interventions were developed 39,40 . These studies helped to screen malnutrition especially in low‐ and middle‐income countries, but were also limited by low network capacity and limited access to mobile phones to specific technical barriers 41–43 .…”
Section: Discussionmentioning
confidence: 99%
“…In the other field of diagnosing genetic diseases, facial‐photograph‐based e‐health technology has also showed it potential 37,38 . In the field of screening malnutrition, more and more mobile phone interventions were developed 39,40 . These studies helped to screen malnutrition especially in low‐ and middle‐income countries, but were also limited by low network capacity and limited access to mobile phones to specific technical barriers 41–43 .…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated larger improvement scores for the intervention group compared to the control group. Based on a recent Iranian systematic review, any education or advice received from influential sources can improve the mean score of self-efficacy in a moderate or strong manner [ 29 , 30 ]. An earlier study evaluated the impact of an educational program and reported a significant difference ( p < 0.01) for breastfeeding self-efficacy mean scores between intervention and control groups [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study has strengths and some potential limitations that need to be considered when interpreting the results. To our knowledge and based on a recent review [48], it is the first randomised controlled trial assessing the effect of smartphone-based maternal nutritional education addressing complementary feeding among undernourished young children of an age characterised by accelerated growth and growth faltering. Due to the low number of dropouts (<10%) and missing values (i.e., those mother-child pairs with some but not all outcomes at follow-up) completers-only analysis was found to be sufficient to assess the research question.…”
Section: Discussionmentioning
confidence: 99%